2021
DOI: 10.1016/j.bbapap.2020.140536
|View full text |Cite
|
Sign up to set email alerts
|

Understanding molecular enzymology of porphyrin-binding α + β barrel proteins - One fold, multiple functions

Abstract: There is a high functional diversity within the structural superfamily of porphyrin-binding dimeric α + β barrel proteins. In this review we aim to analyze structural constraints of chlorite dismutases, dye-decolorizing peroxidases and coproheme decarboxylases in detail. We identify regions of structural variations within the highly conserved fold, which are most likely crucial for functional specificities. The loop linking the two ferredoxin-like domains within one subunit can be of different sequence lengths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 119 publications
1
47
0
Order By: Relevance
“…Dye-decolorizing peroxidases (DyPs; EC 1.11.1.19) are the most recently discovered member of the histidine-heme ligated peroxidase superfamily [1]. They are widespread in bacterial and fungal genomes [2] and represent a distinct heme peroxidase structural family that possess a dimeric α + β barrel fold (SCOP 3,000,089, InterPro Pfam CL0032) capable of binding a single b-type heme [3,4]. DyPs were initially divided into four phylogenetic classes; types A, B, C and D [5], with types C and D later found to be one phylogenetic class and now referred to as C/D-type.…”
Section: Introductionmentioning
confidence: 99%
“…Dye-decolorizing peroxidases (DyPs; EC 1.11.1.19) are the most recently discovered member of the histidine-heme ligated peroxidase superfamily [1]. They are widespread in bacterial and fungal genomes [2] and represent a distinct heme peroxidase structural family that possess a dimeric α + β barrel fold (SCOP 3,000,089, InterPro Pfam CL0032) capable of binding a single b-type heme [3,4]. DyPs were initially divided into four phylogenetic classes; types A, B, C and D [5], with types C and D later found to be one phylogenetic class and now referred to as C/D-type.…”
Section: Introductionmentioning
confidence: 99%
“…In nature, white-rot fungi and certain bacteria are responsible for the depolymerization and conversion of lignin, and therefore, they are useful sources of ligninolytic enzymes, such as laccases and fungal lignin (LiP), versatile (VP), manganese peroxidases (MnP) and dye-decolorizing peroxidases (DyPs) [ 8 , 9 , 10 , 11 ]. DyPs are a family of microbial heme peroxidases that display structural features analogous to chlorite dismutases with an α + β ferredoxin-like fold [ 12 ]. These enzymes show a remarkably broad range of substrates, from synthetic azo and antraquinonic dyes and aromatic sulfides to iron and manganese ions, phenolic and nonphenolic lignin units, wheat straw lignocellulose and kraft lignin, and are therefore interesting enzymes for a vast array of biotechnological applications including bioprocesses targeted at the valorization of lignin [ 9 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…After initial oxidation of coproheme to Compound I (two-electron deficient reaction intermediate), a catalytic tyrosine radical is generated, which is completely essential for both decarboxylation reactions ( Streit et al, 2018 ; Milazzo et al, 2019 ). The tyrosine radical initiates cleavage of a CO 2 molecule from the porphyrin substituent and the formation of a vinyl group by a hydrogen atom abstraction of the β-carbon of the respective propionate ( Celis et al, 2017 ; Hofbauer et al, 2021 ). Mechanistic studies revealed the order of decarboxylation and proved that propionate at position 2 (p2) is decarboxylated first.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we presented that a variant (H118F) of the actinobacterial coproheme decarboxylase from Cornyebacterium diphteriae ( Cd ChdC) accumulates 2-monovinyl-4-monopropionyl deuteroheme, which is the natural intermediate of the native decarboxylation reaction. H118, unique in actinobacterial ChdCds, is part of a flexible loop, linking the N- and the C-terminal domain of one subunit in ChdCs ( Hofbauer et al, 2021 ). In this variant, the catalytic tyrosine (Y135) of Cd ChdC is positioned correctly to facilitate decarboxylation of p2 but due to steric hindrance, the reorientation of the three-propionate intermediate is prohibited and therefore no decarboxylation of p4 occurs ( Sebastiani et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%